Identidades sociales y representaciones políticas en conflicto: el sistema educativo chileno en los Andes de Arica, 1884-1929 - Mondaca, Carlos (2008)
This paper aims to explain and analyze how certain contradictionis manifested in the social identities in the population of the Andeanhighlands of Arica during the process of implementing the post-PacificWar education, specially in its act of incorporating the policies ofthe Chilean education in these territories when there was a renewedresidue of Peruvian citizenship in the everyday act of this Andeanpopulation (currently, northern Chile).In characterizing this process of socio-political and socio-culturalmixtures, I intend to discuss two points: first, that beyond the processitself, there was since before the occupation a Chilean idea of modernityimplemented by a liberal ideology that permeated the wholenineteenth century Peruvian society. Second, that there was a disputeof an education beyond the nationalities in conflict as an articulatingaxis. Since there was a clear involvement of local schools to theirdesignated Andean spaces, I suggest using the idea of modernity thatcould support this proposal.